DEBT TO TOTAL ASSET RATIO, DEBT TO EQUITY RATIO, AND COMPANY’S VALUE WITH ROA AS MEDITATION - Evi Maria; Lidia Andiani (JURNAL MANAJEMEN DAN BISNIS, 2021)
This study analyzes the effect of debt to asset ratio (DAR) and debt to equity ratio (DER) with price earning ratio (PER) and profitability as measured by return on assets (ROA) as the mediating variable. The research was conducted in mining sector companies on the Indonesia Stock Exchange (BEI) with a population of 50 companies. Sampling was done by using purposive sampling method, which takes into account the availability of data during the observation period, namely 2016 - 2019, so 19 companies were selected. The collected data were analyzed using eviews 10. The results of the analysis show that DER has no direct effect on ROA, DAR has a significant and negative effect on ROA, so that increasing DAR will reduce ROA. DAR and DER do not directly affect PER. ROA directly has a positive and significant effect on PER. ROA is not proven to be a variable that mediates the effect between DER, DAR and PER